2019
DOI: 10.3390/ijms20133343
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy Levels of Phthalates and Bisphenol A in Mexican Pregnant Women with Gestational Diabetes and Its Association to Altered Expression of miRNAs Involved with Metabolic Disease

Abstract: Several studies indicate that bisphenol A (BPA) and phthalates may have a role in the development of metabolic diseases using different molecular pathways, including epigenetic regulatory mechanisms. However, it is unclear whether exposure to these chemicals modifies serum levels of miRNAs associated with gestational diabetes mellitus (GDM) risk. In the present study, we evaluated the serum levels of miRNAs associated with GDM (miR-9-5p, miR-16-5p, miR-29a-3p and miR-330-3p) and urinary levels of phthalate met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 62 publications
1
71
1
Order By: Relevance
“…Several circulating miRNAs are dysregulated in patients diagnosed with gestational diabetes mellitus (GDM) during pregnancy (Zhao et al, 2011;Zhu et al, 2015). A study sought to identify the association of BPA and phthalate exposure measured in serum with the expression of circulating miRNAs related to GDM (miR-9-5p, miR-16-5p, miR-29a-3p, and miR-330-3p) revealed higher levels of miR-9-5p, miR-29a-3p, and miR-330-3p of patients with GDM compared to non-diabetic subjects (Martinez-Ibarra et al, 2019). Phthalate metabolites like MBP, mono-isobutyl phthalate (MiBP), mono-benzyl phthalate (MBzP), and MEHP were detected in 97-100% of urine samples and Bisphenol-A (BPA) in only 40% of samples (Martinez-Ibarra et al, 2019).…”
Section: Gestational Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several circulating miRNAs are dysregulated in patients diagnosed with gestational diabetes mellitus (GDM) during pregnancy (Zhao et al, 2011;Zhu et al, 2015). A study sought to identify the association of BPA and phthalate exposure measured in serum with the expression of circulating miRNAs related to GDM (miR-9-5p, miR-16-5p, miR-29a-3p, and miR-330-3p) revealed higher levels of miR-9-5p, miR-29a-3p, and miR-330-3p of patients with GDM compared to non-diabetic subjects (Martinez-Ibarra et al, 2019). Phthalate metabolites like MBP, mono-isobutyl phthalate (MiBP), mono-benzyl phthalate (MBzP), and MEHP were detected in 97-100% of urine samples and Bisphenol-A (BPA) in only 40% of samples (Martinez-Ibarra et al, 2019).…”
Section: Gestational Diabetesmentioning
confidence: 99%
“…A study sought to identify the association of BPA and phthalate exposure measured in serum with the expression of circulating miRNAs related to GDM (miR-9-5p, miR-16-5p, miR-29a-3p, and miR-330-3p) revealed higher levels of miR-9-5p, miR-29a-3p, and miR-330-3p of patients with GDM compared to non-diabetic subjects (Martinez-Ibarra et al, 2019). Phthalate metabolites like MBP, mono-isobutyl phthalate (MiBP), mono-benzyl phthalate (MBzP), and MEHP were detected in 97-100% of urine samples and Bisphenol-A (BPA) in only 40% of samples (Martinez-Ibarra et al, 2019). Thus, phthalates and BPA may play a role in the development of metabolic diseases like GDM via epigenetic regulatory mechanism such as miRNA regulation.…”
Section: Gestational Diabetesmentioning
confidence: 99%
“…Phthalates have been considered obesogens, therefore contributing to overweightness and obesity. It has been shown that exposure to phthalates alters glucose and lipid metabolism, which increases the risk of developing insulin resistance [150,151].…”
Section: Phthalatesmentioning
confidence: 99%
“…22 A more recent study noted that the exposure levels among Mexican pregnant women were 30 times higher than those reported in previous studies. 23 These studies are limited in sample size and target only pregnant women, which highlights the need for information about BPA levels in other Mexican population groups. In addition, in products commonly found in Mexican supermarkets, it has been shown that BPA migrated from the epoxy resin lining tuna and jalapeño cans into the enclosed food; 24 and that BPA is present in baby bottles and microwaveable plastic containers.…”
Section: Mexico Case Studymentioning
confidence: 99%